1989
DOI: 10.1104/pp.90.4.1347
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Systemic Suppression of Nodulation in Split Root Systems of Supernodulating Soybean (Glycine max [L.] Merr.) Mutants

Abstract: Wild-type soybean (Glycine max [LU Merr. cv Bragg) and a nitrate-tolerant supemodulating mutant (nts382) were grown in split root systems to investigate the involvement of the autoregulation response and the effect of timing of inoculation on nodule suppression. In Bragg, nodulation of the root portion receiving the delayed inoculation was suppressed nearly 100% by a 7-day prior inoculation of the other root portion with Bradyrhizobium Japonkum strain USDAI 10. Significant suppression was also observed after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 17 publications
(28 reference statements)
3
77
1
Order By: Relevance
“…veloping nodules and roots before any considerable output of fixed nitrogen from the nodules (Atkins, 1986;Atkins et al, 1989) and also in the absence of mineral nitrogen, which might affect both suppression of nodulation (Olsson et al, 1989), and the allocation of radiolabelled sugar (Olsson et al, 1989) or current photosynthate (Singleton & van Kessel, 1987) to nodulated or nitrogen-fed roots.…”
Section: Relative Partitioning Of Labelled Photosynthate To Roots Andmentioning
confidence: 99%
See 1 more Smart Citation
“…veloping nodules and roots before any considerable output of fixed nitrogen from the nodules (Atkins, 1986;Atkins et al, 1989) and also in the absence of mineral nitrogen, which might affect both suppression of nodulation (Olsson et al, 1989), and the allocation of radiolabelled sugar (Olsson et al, 1989) or current photosynthate (Singleton & van Kessel, 1987) to nodulated or nitrogen-fed roots.…”
Section: Relative Partitioning Of Labelled Photosynthate To Roots Andmentioning
confidence: 99%
“…nature and shoot control of the autoregulatory response in soybean. Caetano-AnoUes and Gresshoff (1990 postulated that early rhizobial infections induce the synthesis of a shoot-derived inhibitor (SDI), which then suppresses nodule development from later infections, Supernodulating soybean mutants apparently lack, or have much decreased, synthesis of SDI (Olsson et al, 1989. Francisco & .\kao, 1993, Francisco & Harper, 1995, Recent results of Francisco & Harper (1995) suggest that inhibitory compound(s), synthesized in the leaf, control nodulation phenotype independently of the root, Francisco & Akao (1993) proposed a late-acting nodulation control mechanism that is apparently unrelated to autoregulation and is observed in wild type and in supernodulating soybean, Kosslak & Bohlool (1984) used different levels of shading to show that nodule number per plant and the intensity of the regulatory response were directly related to the amount of photosynthetically active radiation available to soybean.…”
mentioning
confidence: 99%
“…The initial step of autoregulation is thought to involve longdistance signalling from the root to the shoot [5][6][7] . This hypothesis was strongly supported by the findings from analyses of the Lotus japonicus hypernodulating mutant, hypernodulation aberrant root formation (har1) [8][9][10] , and orthologous mutants in other leguminous species 8,9,11,12 .…”
mentioning
confidence: 99%
“…Using split-root experiments, Kosslak & Bohlool (1984) have shown that inoculation of one side of the root system suppressed subsequent development of nodules on the other side. Olsson et al (1989) showed that this suppression of nodulation by the inoculated side of a split-root system was substantially reduced in supernodulating nts1 mutant plants that lack regulation of the shoot-root signal. Presumably, the root-derived signal elicits a response in the shoot that allows completion of the autoregulation loop via transmission of a signal to the root (Fig.…”
Section: Long-distance Signalling Systemsplant Hormones In Search Of mentioning
confidence: 99%